The Use of Problem Based Learning in Improving Students’ Speaking Skill - Resy Oktadela; Yusti Elida (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to develop a model of PBL ( Problem Based Learning) in English teaching . It belongs to research and development (R D), which includes research and information collection, planning, developing preliminary form of product, preliminary field testing, product revision, field testing, operational product revision, field operational testing, final product revision, and dissemination and implementation. Based on the stages of R D, the findings can be explained as follows. Firstly, based on the study of the concept of PBL model, five stages proposed by Glickman were implemented, namely: (1) pre-conference with the lecturer; (2) classroom observations; (3) the analysis and interpretation of the observation results and set up the konverensi approach; (4) meetings after observing; (5) evaluating the four stages. All stages were carried out by utilizing information. Secondly,students’ and lecturer’s perception or understanding on PBL model is yet complete. Thirdly, PBL Model based on the character can be considered as a breakthrough for guiding teachers to improve their teaching competence.